N‐Acetyl Cysteine Is Associated With Dopaminergic Improvement in Parkinson's Disease. Issue 4 (17th July 2019) - Monti, Daniel A.; Zabrecky, George; Kremens, Daniel; Liang, Tsao‐Wei; Wintering, Nancy A.; Bazzan, Anthony J.; Zhong, Li; Bowens, Brendan K.; Chervoneva, Inna; Intenzo, Charles; Newberg, Andrew B.
Abstract : This study assessed the biological and clinical effects in patients with Parkinson's disease (PD) of N‐acetyl‐cysteine (NAC), the prodrug tol ‐cysteine, a precursor to the natural biological antioxidant glutathione. Forty‐two patients with PD were randomized to either weekly intravenous infusions of NAC (50 mg/kg) plus oral doses (500 mg twice per day) for 3 months or standard of care only. Participants received prebrain and postbrain imaging with ioflupane (DaTscan) to measure dopamine transporter (DAT) binding. In the NAC group, significantly increased DAT binding was found in the caudate and putamen (mean increase from 3.4% to 8.3%) compared with controls ( P  < 0.05), along with significantly improved PD symptoms ( P  < 0.0001). The results suggest NAC may positively affect the dopaminergic system in patients with PD, with corresponding positive clinical effects. Larger scale studies are warranted.